Montaje de una malla de puesta a tierra ubicada en instalaciones de la Institución Universitaria Pascual Bravo (2015)
Abstract: The main objective of this project is the construction of the grounding system in the University Pascual Bravo Institute of Medellin, which guarantees the safety and security during power failures, but also serve as a means of dissipation currents within the earth so as not to exceed the operating limits of the equipment. The design of this system grounding (SPT), was calculated from measurements of soil resistivity and the assumption of a model of the soil, the amount of driver and rods installed. The soil type is a decisive factor in the design of SPT, where we know if it is suitable to use it, knowing if the ground is wet, dry or what kind of land belongs factor. The grounding systems are systems that currently reversed great importance in protecting and normal operation of various electrical and electronic systems, mainly in the security of the people who are in contact or in areas of influence of electrical systems. This is a model that has a non-uniform soil represents a simple way of studying land before designing a system Grounding, because at the time of the study, the ground was with different kind of resistance shows a simple design so that not only depends on calculating the net as such, it is vital to know what kind of soil we will meet. Technological advances and new techniques for troubleshooting minimizing electrical shock that can advance, but as for the SPT, is something that more technology to emerge is the same process to implement it. In the university Pascual Bravo prototype simulator or soil resistivity for dissipating fluctuating currents had not; for students has always been the theory of systems Grounding but never has given a practical class with a prototype, this project significant progress is achieved, whereby students will have the opportunity to practice and know how one Tellurometer, what kind of resistance is the ground, like a grounded mesh is constructed, among others is used.